2014
DOI: 10.1111/jace.12850
|View full text |Cite
|
Sign up to set email alerts
|

Nanodomains in KNN‐Based Lead‐Free Piezoelectric ceramics: Origin of Strong Piezoelectric Properties

Abstract: Excellent piezoelectric properties of d 33 * = 768 pm/V and strain = 0.07% at 1 kV/mm, were obtained by lead-free in (Na 0.52 K 0.4425 Li 0.0375 )(Nb 0.86 Ta 0.06 Sb 0.08 )O 3 ceramics. They displayed good temperature stability up to 200°C. Significantly enhanced piezoelectricity originated from nanodomains of width 20-30 nm, and the result was confirmed by transmission electron microscopy. The above-mentioned nanodomains emerged because of low domain wall energy near polymorphic phase transition regions and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 22 publications
1
41
1
Order By: Relevance
“…However, it was later found that the property enhancement was not due to a classical MPB, but a polymorphic phase transition (PPT) between the tetragonal and orthorhombic phases56. Even so, domains were found to miniaturize down to the nanometer scale in the two-phase coexistence region of the KNN-based ceramics789, in a similar manner to that observed in the MPB region of many other piezoelectric materials10111213.…”
mentioning
confidence: 75%
“…However, it was later found that the property enhancement was not due to a classical MPB, but a polymorphic phase transition (PPT) between the tetragonal and orthorhombic phases56. Even so, domains were found to miniaturize down to the nanometer scale in the two-phase coexistence region of the KNN-based ceramics789, in a similar manner to that observed in the MPB region of many other piezoelectric materials10111213.…”
mentioning
confidence: 75%
“…[3][4][5] To obtain a good performance in KNN-based piezoceramics, various attempts such as compositional modification, adopting advanced synthesizing technology, and creating the textured microstructure have been made in the last decade. 2,[6][7][8][9] However, their large-scale practical applications are still restricted by some factors, such as the poor reproducibility, which usually occurs in the complex synthesis procedure or complicated composition, the weak thermal stability, and so on. 2,3,10,11 The piezoelectricity of KNN-based ceramics lacks temperature stability mainly because its enhancement is realized through polymorphic phase transition (PPT), which is adjusted nearly room temperature whereby two phases coexist.…”
Section: Introductionmentioning
confidence: 99%
“…However, the nano‐domains (~70 nm) with lower E w should play an important role in increasing the piezoelectric response. The contribution from the nano‐domains is the origin for the high piezoelectric properties in KNN‐based ceramics, which has been verified previously . Thus, the nano‐domains (~70 nm) in the ceramics at z = 0.02 are the origin for the high piezoelectric properties of KNNTaz‐0.045BNZ+0.4Mn ceramics.…”
Section: Resultsmentioning
confidence: 99%